Physicochemical, sensory and moisture sorption properties of centrifuge-heated virgin coconut oil - Agunday, Francis John Pantino (2007)
ABSTRACT The study aimed to establish the optimal extraction process for the centrifuge-heated VCO and subsequently determine it's physicochemical, sensory and moisture sorption properties using the modified Gonzaga process. Three treatments namely: single continuous extraction for 3 hours (T1) and 5 hours (T3) and combined extracts from the separate heating (T2) were evaluated to determine the optimal extraction process. Moreover, the optimized sample using bench scale production was assessed in terms of physicochemical, sensory characteristics and moisture sorption properties. The single continuous extraction for five hours (T3) was established as the optimal extraction process. The physicochemical characteristics of the samples from bench-scale production showed no significant (p<0.05) deviations with the exception of the percent yield with respect to coconut meat and coconut milk. Sensory data for all samples showed no perceptible color,turbidity, acidity and rancidity but with moderately perceptible nutty aroma, which is a characteristic of VCO extracted involving heat treatment. Furthermore, the VCO samples showed high degree of stability up to 90% relative humidity with the monomolecular layer established at 0.0272 g water per g VCO.